Needs of Omani Youth in the Small and Medium Enterprises Sector - Alhaj, Amjad; Al Busafi, Majid; AL Hashemi, Amal (Dirasat: Human and Social Sciences, 2022)
The study aims to identify the reality of interest in small and medium enterprises (SMEs) in Oman, to reveal the needs of young people in the SME sector in Oman, and to identify Oman's vision 2040 and its role in promoting work in SMEs. The study relies on the descriptive approach, in order to suit the objectives and questions of the study, and is applied to a number of small and medium entrepreneurs: (218) individuals. The study relies on the questionnaire tool as a key tool for data collection, which includes closed and open questions with a view to obtaining data to answer the study questions. The study proves that the need to provide financial support, facilitate access to loans and the need for government support are the greatest needs of young people in SMEs. The study also shows that there is an urgent need to facilitate procedures for clearing transactions and exempting taxes and interests. The study recommends the importance of diversifying the sources of financial support for these institutions, and the need to find a system and policy to support, activate, and protect small and medium enterprises in the event that the project falters or goes through a major problem that may lead to closure and bankruptcy.